Enhance the Efficiency of Enterprise Management Based on Big Data and Intelligent Informationization - Xiaohao Yan (Forest Chemicals Review, 2022)
In this paper, based on big data, an intelligent enterprise management system is designed. It usesa management application innovation module to realize enterprise intelligent management application innovation through multiple screen interaction methods. Then data analysis technologies such as data processing and data cleaning are used to findthe hidden information, timely understand customer behavior and requirements, and improve enterprises’ product sales. The experimental results show that the expected results of the system testing are the same as the actual results. When the proposed system is used for enterprise management, the maximum throughput of the system is 290 000 Mb/s, and the average response time is 3.5s. Therefore, the experimental data indicate that the proposed system can achieve efficient enterprise intelligent management.